Cellular and humoral immunity in prostitutes in Istanbul - (:unkn) unknown (My University, 1988)
Acquired immunodeficiency syndrome (AIDS) can be transmitted through heterosexual intercourse and prostitutes may be responsible for this form of transmission. Thirty-four prostitutes were included in this study and their humoral and cellular immunological parameters were compared with control group. Prostitutes were divided in two subgroups according to their sexual practice and the use of illicit drugs and compared with each other. The only immunological parameter that is significantly different from the control group was the serum IgM level. In prostitutes who have more than 11 partners in a week, the mean number of E rosettes, EAC rosette forming cells and cells expressing surface immunoglobulins were significantly higher than prostitutes who have 0-10 sexual partner in a week.
Keywords: Adult; Female; Humans; Turkey; Immunity; Acquired Immunodeficiency Syndrome; Immunity, Cellular; Receptors, Antigen, B-Cell; Rosette Formation; Sex Work; Sexual Behavior; Sexual Partners